Evaluation of NOₓ emission and dispersion from marine ships in Klaipeda sea port - Abrutytė, Eglė; Žukauskaitė, Audronė; Mickevičienė, Rima; Zabukas, Vytenis; Paulauskienė, Tatjana (Journal of Environmental Engineering and Landscape Management, 2014)
The aim of the presented research was to assess the NOx emission and dispersion from marine ships in Klaipeda sea port. NOx emissions from ships operating in Klaipeda sea port were calculated using the Lloyd's Register detailed ship movement method, after collecting the information about technical characteristics of each marine ship visiting the port and the time spent staying in the port. After calculating the emission, the modelling using AERMOD software was completed and the dispersion of pollutants over different seasons of the year was determined. When performing the evaluation of NOx emissions it was estimated, that most of these pollutants enter the atmosphere from stationary vessels moored to quays with active auxiliary motors; this accounts even for up to 72% of the total NOx emission from marine ships in Klaipeda port. It was calculated that a total of 945.6 tons of NOx compounds enter the air basin from ships which operate in Klaipeda port. It was determined that the seasonality and meteorological conditions are a significant factor affecting the dispersion of pollutants. During winter time, a higher dispersion of pollutants is typically found at the source of contamination, and in the summer pollutants are decomposed more quickly and their concentrations as formed above the port are 30% lower, however, 40-50% higher concentrations are formed over the Klaipeda city residential districts.First published online: 21 May 2014